(untitled) (Zaporizhzhia Historical Review, 2021)
This article is devoted to the relevant subject of correlation of cross type, typological image and and its function structure. Definition is given to Georgian and anchorlike types of crosses, its role-defining category is underlined for Christian momument identification with its denomination. The author emphasizes that cross architectonics predetermines its originality, recreating peculiarity of craftsman and that one this stavros is facing and whom it can be devoted to. Theoretic speculations are strengthened by deep analysis of sacral art works.